Bioavailability of everolimus administered as a single 5 mg tablet versus five 1 mg tablets: a randomized, open-label, two-way crossover study of healthy volunteers - Thudium K; Gallo J; Bouillaud E; Sachs C; Eddy S; Cheung W (Dove Medical Press, 2015)
Karen Thudium,1 Jorge Gallo,2 Emmanuel Bouillaud,2 Carolin Sachs,2 Simantini Eddy,1 Wing Cheung1 1Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA; 2Novartis Pharma AG, Basel, Switzerland Background: The mammalian target of rapamycin (mTOR) inhibitor everolimus has a well-established pharmacokinetics profile. We conducted a randomized, single-center, open-label, two-sequence, two-period crossover study of healthy volunteers to assess the relative bioavailability of everolimus administered as one 5 mg tablet or five 1 mg tablets. Methods: Subjects were randomized 1:1 to receive everolimus dosed as one 5 mg tablet or as five 1 mg tablets on day 1, followed by a washout period on days 8–14 and then the opposite formulation on day 15. Blood sampling for pharmacokinetic evaluation was performed at prespecified time points, with 17 samples taken for each treatment period. Primary variables for evaluation of relative bioavailability were area under the concentration–time curve from time zero to infinity (AUCinf) and maximum blood concentration (Cmax). Safety was assessed by reporting the incidence of adverse events (AEs). Results: Twenty-two participants received everolimus as one 5 mg tablet followed by five 1 mg tablets (n=11) or the opposite sequence (n=11). The Cmax of five 1 mg tablets was 48% higher than that of one 5 mg tablet (geometric mean ratio, 1.48; 90% confidence interval [CI], 1.35–1.62). AUCinf was similar (geometric mean ratio, 1.08; 90% CI, 1.02–1.16), as were the extent of absorption and the distribution and elimination kinetics. AEs, all grade 1 or 2, were observed in 54.5% of subjects. Conclusion: Although the extent of absorption was similar, the Cmax of five 1 mg tablets was higher than that of one 5 mg tablet, suggesting these formulations lead to different peak blood concentrations and are not interchangeable at the dose tested. Keywords: absorption kinetics, healthy volunteers